Review of international practice of health care provider network planning - V. V. Omelyanovskiy; D. V. Lukyantseva; N. N. Sisigina (Фармакоэкономика, 2022)
Objevtive: to identify and systematize the main approaches to planning health care provider network used in foreign countries.Material and methods. Preliminary search for countries who had an experience of systematical planning of health care provider network and tools that they used for planning was conducted in regular health system reviews made by the European Observatory on Health Systems and Policies. Identified tools became a subject of general Internet search for the official publications about goals, mechanisms and results of their usage. The findings were analysed to reveal the similarities and differences between national health care provider network planning policies as well as the objective preconditions for the formation of such policies.Results. Three main approaches to health care provider network planning were identified in the analysis: (1) through establishing state-owned health care providers, (2) through granting the right to deliver guaranteed health care or (3) through granting the right to deliver health care of all categories. A close relationship between the choice of prevailing approach to planning and specific planning tools and the national health care model and structure of health services supply was shown. The typical policy of countries most similar to Russia on these parameters (“young” insurance systems, operating under conditions of predominant state supply of medical services) is the protection of key providers on the basis of minimum activity or income guarantees with the gradual development of a competitive health care market based on the rest of the Compulsory Health Insurance program.Conclusion. Current Russian health care provider network planning regulation based on the direct control over the state-owned health care providers does not correspond to the changed health care model and does not allow taking full advantages of the social health insurance. The results of the review can be used to develop new tools for planning health care provider network spanning on non-state providers.